GROWTH AND YIELD OF OKRA (ABELMOSCHUS ESCULENTUS) AS INFLUENCED BY SEED WEIGHT - U. THAPA; A. K. RAI; R. CHAKARBORTY (The Bioscan, 2012)
A field experiment was conducted during Kharif seasons in 2010, to evaluate the growth and yield response of okra at varying seed weight and determine the optimal seed weight that will maximise the marketing yield. Four varieties of okra have taken in consideration for this investigation viz. Sagum, Satsira, Arka Anamika, and Parbhani Kranti. The result indicated that in all the four varieties, the lowest seed weight was inferior to other seed weight grades. The light seeds showed significantly lower germination percentage (71.83) than the heavy seeds (80.50). Heavy seed weight recorded maximum root (8.19cm) and shoot length (13.19cm) and minimum of days required for opening of cotyledons leaf (5.08) and first true leaf (9.60). Other growth parameters like plant height and number of leaves at different stages varied significantly between the seed weight grades and varieties. Among the varieties, maximum yield of 10.5t/ha. was obtained from Arka Anamika with heavy seed weight.